Effect of a Topical Combination of Latanoprost and Pranoprofen on Intraocular Pressure and the Ocular Surface in Open-Angle Glaucoma Patients - Simin Zhu; Dabo Wang; Jing Han (Journal of Ophthalmology)
Objective. A prospective study was performed to observe the effects of nonsteroidal anti-inflammatory drug (NSAID) eyedrops on intraocular pressure (IOP) and the ocular surface in primary open-angle glaucoma (POAG) patients treated with 0.005% latanoprost eyedrops. Methods. Forty-eight subjects were randomized into two study groups (NSAID and control). Latanoprost was continued for 10 weeks in all subjects. At the end of week 4, pranoprofen was added in the NSAID group, and treatment lasted for 4 weeks, whereas patients in the control group were treated with latanoprost alone. IOP was measured in both groups every 2 weeks, and the changes in the ocular surface in the NSAID group were evaluated once a month. Results. Pranoprofen addition resulted in a decrease in IOP in the NSAID group compared to the control group (p<0.01). After pranoprofen was discontinued, IOP significantly increased in the NSAID group (p<0.01), remaining approximately at the same IOP as when they were being treated with latanoprost alone. During the same examination, no significant variations in IOP were found in the control group. Patients who were treated with latanoprost alone showed gradual improvements in ocular surface symptom scores and conjunctival hyperemia scores during the first four weeks of treatment (p<0.01). When pranoprofen eyedrops were added, ocular surface symptom scores decreased (p<0.01), but conjunctival hyperemia scores did not change significantly. Conclusions. For POAG patients treated with latanoprost, the combination of pranoprofen can not only significantly enhance the latanoprost-induced IOP-lowering effect but also relieve the uncomfortable ocular symptoms caused by latanoprost.